Giant magnetoresistance control and nontrivial metallic state manipulation in a transition-metal dichalcogenide spin-valve using a gate voltage. (15th November 2018) - Bai, Chunxu; Yang, Yanling; Bai, Lin
Abstract: Here, we have theoretically studied the valley- and spin-resolved transport in a monolayer transition metal dichalcogenides based spin valve device, where both the Rashba spin orbit interaction and a gate voltage coexist in the central lead. In contrast to conventional semiconductor, nontrivial metallic states, such as, normal Rashba metal state (NRMS), anomalous Rashba metal state (ARMS), and Rashba ring metal state (RRMS), can be generated and manipulated by Rashba spin orbit interaction without the magnetic effect. For a nonferromagnetic double junction, it was found that the valley- and spin-resolved tunneling conductance can be effectively tuned by the incident energy, the junction length, the Rashba spin orbit interaction strength, and the gate voltage. Due to the spin texture and the Fermi wavevectors in the central lead, both the tunneling coefficient and the tunneling conductance all exhibit the remarkable characteristic features which enable us to diagnose the special states. For a ferromagnetic spin valve device, the resulting nontrivial metallic groundstates in the central lead also demonstrate directly in the giant magnetoresistance with notable unique features. We have further revealed that a perfect valley and spin giant magnetoresistance stems from the spin splitting and the spin-valley coupling. These valley- and spin-resolved phenomena are interesting for both fundamental research and applications.